The quality of drinking and domestic water from the surface water sources (lakes, rivers, irrigation canals and ponds) and springs in cholera prone communities of Uganda: an analysis of vital physicochemical parameters - Godfrey Bwire; David A. Sack; Atek Kagirita; Tonny Obala; Amanda K. Debes; Malathi Ram; Henry Komakech; Christine Marie George; Christopher Garimoi Orach (BMC, 2020)
Abstract Background Water is the most abundant resource on earth, however water scarcity affects more than 40% of people worldwide. Access to safe drinking water is a basic human right and is a United Nations Sustainable Development Goal (SDG) 6. Globally, waterborne diseases such as cholera are responsible for over two million deaths annually. Cholera is a major cause of ill-health in Africa and Uganda. This study aimed to determine the physicochemical characteristics of the surface and spring water in cholera endemic communities of Uganda in order to promote access to safe drinking water. Methods A longitudinal study was carried out between February 2015 and January 2016 in cholera prone communities of Uganda. Surface and spring water used for domestic purposes including drinking from 27 sites (lakes, rivers, irrigation canal, springs and ponds) were tested monthly to determine the vital physicochemical parameters, namely pH, temperature, dissolved oxygen, conductivity and turbidity. Results Overall, 318 water samples were tested. Twenty-six percent (36/135) of the tested samples had mean test results that were outside the World Health Organization (WHO) recommended drinking water range. All sites (100%, 27/27) had mean water turbidity values greater than the WHO drinking water recommended standards and the temperature of above 17 °C. In addition, 27% (3/11) of the lake sites and 2/5 of the ponds had pH and dissolved oxygen respectively outside the WHO recommended range of 6.5-8.5 for pH and less than 5 mg/L for dissolved oxygen. These physicochemical conditions were ideal for survival of Vibrio. cholerae. Conclusions This study showed that surface water and springs in the study area were unsafe for drinking and had favourable physicochemical parameters for propagation of waterborne diseases including cholera. Therefore, for Uganda to attain the SDG 6 targets and to eliminate cholera by 2030, more efforts are needed to promote access to safe drinking water. Also, since this study only established the vital water physicochemical parameters, further studies are recommended to determine the other water physicochemical parameters such as the nitrates and copper. Studies are also needed to establish the causal-effect relationship between V. cholerae and the physicochemical parameters.